2019
DOI: 10.1016/j.jcot.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Osseointegration of osteoporotic bone implants: Role of stem cells, Silica and Strontium - A concise review

Abstract: Osteoporotic fracture treatment has become a skeletal reconstructive challenge due to accelerated bone turnover and impaired bone regeneration potential. Poor osseointegration ability of the osteoporotic bone usually results in implant pull out and failure. Adoption of conventional bone fracture treatment strategies like autografts and allografts have limited applications in such pathological conditions. Hence biomaterials functionalised with therapeutic ions or drugs may be adopted to aid the delivery of ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…Inflammatory cells (macrophages, monocytes, lymphocytes, and polymorphonuclear cells) and fibroblasts infiltrate bone tissue in a process mediated by prostaglandins [ 11 ]. Throughout fracture repair, mesenchymal stem cells (MSCs) from the bone marrow are engage at the fracture site in interaction with the local cells influencing the healing efficacy [ 7 ]. The emergence of intramembranous bone starts right away at the cortical tissue and periosteum.…”
Section: Bone Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Inflammatory cells (macrophages, monocytes, lymphocytes, and polymorphonuclear cells) and fibroblasts infiltrate bone tissue in a process mediated by prostaglandins [ 11 ]. Throughout fracture repair, mesenchymal stem cells (MSCs) from the bone marrow are engage at the fracture site in interaction with the local cells influencing the healing efficacy [ 7 ]. The emergence of intramembranous bone starts right away at the cortical tissue and periosteum.…”
Section: Bone Tissuementioning
confidence: 99%
“…Calcium phosphate scaffolds show the capacity to promote osteogenesis and osteointegration, due to their surface charge, and, also, their chemistry and topography [ 4 ]. HA coated implants are proven to promote osteointegration capacity of inert metals [ 7 ] but some pioneering works were reported related to COLL/HA composite deposition by using MAPLE [ 54 ]. Due to its high biocompatibility, bioactivity, osteoconductive and/or osteoinductive capacity (in certain conditions), nontoxicity, nonimmunogenic properties, and noninflammatory behavior, HA is available and used as a bone filler and as coatings on prostheses, [ 4 ].…”
Section: Biomaterials Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The representative treatment is strontium ranelate; however, a series of undesirable side effects cannot be ignored for long-term systematic treatment. 6 Studies have indicated that strontium (Sr) serves as one of the most efficient trace elements for bone metabolism due to its strong bone-seeking properties, 7 and it can also inhibit osteoclast function. 8,9 Nonetheless, while studies have mainly focused on the applications of pharmacological agents in the field of osteoporosis, less attention has been paid to site reconstruction of osteoporotic-related bone defects or fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing clinical demand for bone regeneration and repair in the context of our ageing population poses a challenge both to healthcare providers and society (Iaquinta et al 2019 ). There is also increasing demand for the implant osseointegration, which is crucial for successful implantology in both orthopaedics and dentistry (Chandran and John 2019 ; Liu et al 2019 ). Tissue engineering provides a promising strategy to meet this clinical demand by developing functional bone construct using stem/stromal cells, biomimetic biomaterial scaffolds, with/without growth factors (Abdulghani and Mitchell 2019 ).…”
Section: Introductionmentioning
confidence: 99%